Pengaruh Penggunaan Kompos Limbah Teh PT. Gunung Slamat Slawi, Terhadap Pertumbuhan Tanamanan Packcoy (Brassica Rapa L.) Dan Kangkung (Ipmoea Aquatic) - Nia Elfiana; Bayu Widiyanto; Antika Tafrijiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to determine (1) the effect of using tea waste compost fertilizer on the growth of packcoy plants, (2) the effect of using tea waste compost fertilizer on the growth of water spinach plants (Ipomea Aquatic), and (3) comparing the effectiveness of tea waste compost fertilizer in cultivating water spinach. and packcoy. The research was carried out from March to May 2023 on the land of PT. Mount Slamat, Slawi. This research used a Completely Randomized Design (CRD) with 4 treatments and 3 repetitions, each treatment namely K0 (control), K1 (150 g), K2 (350 g) and K3 (450 g). The parameters of this research are plant height, number of leaves, and plant weight when the plants are 30 days after planting. The data were analyzed using analysis of variance (ANOVA). The results of the research show that (1) The effect of tea waste compost fertilizer on the growth of packcoy plants has a real influence on the growth of plant height, number of leaves and weight of packcoy plants. K2 treatment with a dose (350 g) showed the best results for average plant height (24.1 cm), number of leaves (17 pieces) and plant weight (29.6 grams). (2) The effect of tea waste compost fertilizer on the growth of kale plants has a significant effect on the growth of plant height, number of leaves and weight of kale plants. K2 treatment with a dose (350 g) showed the best results for average plant height (58.6 cm), number of leaves (50.3 pieces) and plant weight (44.5 grams). (3) Comparing the effectiveness of tea waste compost fertilizer in cultivating water spinach and packcoy varies depending on various factors, including the composition of tea waste, growing conditions, and plant nutritional needs.